A Baroque celebration with Natalie Dessay, Philippe Jaroussky, Patricia Petibon, Rolando Villazón, Anne Sofie von Otter ... with the Concert d'Astrée under the baton of Emmanuelle Haïm - Rameau, Jean-Philippe 1683-1764; Handel, George Frideric 1685-1759; Handel, George Frideric 1685-1759; Rameau, Jean-Philippe 1683-1764; Rameau, Jean-Philippe 1683-1764; Rameau, Jean-Philippe 1683-1764; Rameau, Jean-Philippe 1683-1764; Purcell, Henry 1659-1695; Purcell, Henry 1659-1695; Handel, George Frideric 1685-1759; Handel, George Frideric 1685-1759; Handel, George Frideric 1685-1759; et al. (Sounding images, 2011)
The Concert d'Astrée celebrates its first decade with a concert featuring an elite group of singers, stars specialized in the baroque repertoire or in bel canto opera like Natalie Dessay, Philippe Jaroussky, Rolando Villazón, and Anne Sofie von Otter. Emmanuelle Haïm--founder, director, and harpsichordist of this ensemble dedicated to performance of the baroque opera repertoire--brings together these artists for a recital featuring jewels by three brilliant 18th century composers of opera: Handel, Purcell, and Rameau. A celebratory program sure to astonish and delight!
Keywords: Operas; Music; Music -- 17th century; Music -- 18th century; Operas -- Excerpts; 1600-1799; Excerpts; Concert films; Internet videos